Elderly’s feedback on the service quality of urban green open space in Penang as a catalyst for health and lifestyle resilience - Muhamad Ferdhaus,; Hasnizam Ab Dulhamid,; Halmi Zainol, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sustaining health, social involvement, reducing institutionalization, and enhancing the quality of life of the elderly are community health challenges of the 21st era. Elderly citizens may endure numerous health illnesses due to their vulnerability to many physical and mental intrusions. Quality of life in elderly people can be affected by many environmental and physical factors. The quality of life for the elderly is partially and intimately related to their usage of green open space. The usage of this space will directly affect their health and lifestyle resilience. After this, the significance of getting more understanding and feedback about service quality in urban green open spaces is necessary. This research is aimed to study the link between elderly satisfaction and service quality of the urban green open space. Hence, this research aims to examine the catalyst for health and lifestyle resilience. The participants surveyed in this study were elderly people who were living in the surrounding community and come voluntarily to the urban green open space to use and enjoy all the facilities and activities that had been provided. The outcomes from this research deliver a platform for local authorities and developers in Malaysia to understand elderly expectations and behavior and how it affects their health and lifestyle resilience. The understanding is essential for planning and designing more inclusive, comprehensive and age-friendly urban green open space or parks, which should meet the needs, demand and expectations of older adults and encourage them to engage and participate in more activity.